PENGARUH TRANSFER PRICING, LEVERAGE DAN PROFITABILITAS TERHADAP TAX AVOIDANCE - Nur Alfi Laila Sifai Ghasani; Nurdiono Nurdiono; Yenni Agustina; A. Zubaidi Indra (Jurnal Akuntansi dan Keuangan (JAK), 2021)
The research aims to examine the effect of transfer pricing, leverage, profitability on tax avoidance. the sample in this study was selected using purposive sampling and obtained 140 samples of companies listed on Indonesia Stock Exchange in 2014- 2019 that met the criteria. The result of hypothesis testing with multiple linear regression analysis using the SPSS 23 application show that transfer pricing has not effect on tax avoidance. leverage and profitability has a significant effext with a negative coefficient on tax avoidance.